"Trolls" or "warriors of faith"?: Differentiating dysfunctional forms of media criticism in online comments. Issue 1 (19th December 2019) - Eberwein, Tobias
Abstract : Purpose: The idea that user comments on journalistic articles would help to increase the quality of the media has long been greeted with enthusiasm. By now, however, these high hopes have mostly evaporated. Practical experience has shown that user participation does not automatically lead to better journalism but may also result in hate speech and systematic trolling – thus having a dysfunctional impact on journalistic actors. Although empirical journalism research has made it possible to describe various kinds of disruptive follow-up communication on journalistic platforms, it has not yet succeeded in explaining what exactly drives certain users to indulge in flaming and trolling. This paper intends to fill this gap. Design/methodology/approach: It does so on the basis of problem-centered interviews with media users who regularly publish negative comments on news websites. Findings: The evaluation allows for a nuanced view on current phenomena of dysfunctional follow-up communication on journalistic news sites. It shows that the typical "troll" does not exist. Instead, it seems to be more appropriate to differentiate disruptive commenters according to their varying backgrounds and motives. Quite often, the interviewed users display a distinct political (or other) devotion to a certain cause that rather makes them appear as "warriors of faith." However, they are united in their dissatisfaction with the quality of the (mass) media, which they attack critically and often with a harsh tone. Originality/value: The study reflects these differences by developing a typology of dysfunctional online commenters. By helping to understand their aims and intentions, it contributes to the development of sustainable strategies for stimulating constructive user participation in a post-truth age.